Nghiên cứu ứng dụng trong nông nghiệp vật liệu giữ nước từ tinh bột chế tạo bằng kỹ thuật bức xạ - Nguyễn, Duy Hạng (Trường Đại học Đà Lạt, 2013)
In this work we were interested in the study of radiation modification of water absorbtion of starch by grafting with acrylic acid. The study polymer can absorb water up to 500 times its weight.We also realised the first study of the behavior of selected plants in the melange of a soil and ahydrophylic polymer.